Quo Vadis Pemikiran Politik Islam: Reformulasi Studi Pemikiran Politik Islam - Muhammad Rizky HK (UIN Mataram, 2021)
This article will discuss the possibility to reformulate the Islamic political thought studies. As a part of both; Islamic Studies, and Political Studies, Islamic Political Thought has been dramatically improved with dialectical moves. The dialectical interaction between Islam as a doctrinal side, with politics which has been known as a more ‘humanist’ side has created some perplexed among the scholar. This article explains the ambiguity of the relation between Islam and Political Studies and offer a new formula to re-build the Islamic Political Thought Studies. The Authors tried to reformulate the Islamic Political Thought Studies with Reciprocal Integration, by using Ian Barbour’s theory about the relation between science and religion, Thomas Kuhn’s Theory about Normal Science, Keith Ward’s theory about The Development of Religion, and Amin Abdullah’s theory about integration-interconnection. This article use qualitative research method with descriptive analysis approach through the collection of related literature studies especially.